2009
DOI: 10.2139/ssrn.1509509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ESCO Activities Using Country Indicators

Abstract: Energy Service Companies (ESCOs) are private sector instruments that offer energy-/emission-improvement (energy saving, energy efficiency, energy conservation, emission reduction) projects in the developed and in some developing countries. Literature reveals that energy-/emission-improvements of countries may be related to their innovation-and R&D-activity levels. In this work, we use a literature data on the activities and the sectors targeted by ESCOs in 38 countries, summarized in terms of the age of ESCO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Historically, the energy service market in Sweden has, however, grown quite slowly in terms of sales in relation to high expectations (Bergmasth & Strid, 2004). This also holds for many other international markets (see, e.g., Bertoldi et al, 2006;Okay & Akman, 2010;Painuly et al, 2003;Vine, 2005). In their thesis, Bergmasth and Strid (2004) found that the demand for energy services at the time of their research was weak, that energy companies did not always have the expertise to develop energy services, and that for some types of advanced energy services the high transaction costs constitute a barrier.…”
Section: The Energy Service Market In Swedenmentioning
confidence: 95%
See 1 more Smart Citation
“…Historically, the energy service market in Sweden has, however, grown quite slowly in terms of sales in relation to high expectations (Bergmasth & Strid, 2004). This also holds for many other international markets (see, e.g., Bertoldi et al, 2006;Okay & Akman, 2010;Painuly et al, 2003;Vine, 2005). In their thesis, Bergmasth and Strid (2004) found that the demand for energy services at the time of their research was weak, that energy companies did not always have the expertise to develop energy services, and that for some types of advanced energy services the high transaction costs constitute a barrier.…”
Section: The Energy Service Market In Swedenmentioning
confidence: 95%
“…Existing energy service research to date has focused on describing actual service usage in various countries, regions, and sectors (see, e.g., Bertoldi et al, 2006;Okay & Akman, 2010;Painuly et al, 2003;Vine, 2005). Although these studies have found some growth in energy services, this is still deemed slow and insufficient (Pätäri & Sinkkonen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study [40], carried out in 38 countries, a positive correlation was found between the ESCO indicators (age of ESCO market, number of ESCO companies, total value of ESCO projects and the percentage of the sectors targeted by ESCOs) and socioeconomic indicators (countries per-capita GDPs, energy consumptions and CO 2 emissions). Moreover, in richer countries, ESCOs find more opportunities in the commercial and municipal sectors [40].…”
Section: The Incentive Scheme: White Certificates and Energy Saving Cmentioning
confidence: 93%
“…Improving energy efficiency thus signifies a more efficient utilization of resources, and one way to improve energy efficiency in the energy system is by undertaking investments in energy services. Although the energy service concept was introduced in the early 1980s (Okay and Akman, 2010), today this concept is characterized by definitional confusion (Marino et al, 2011;Pätäri and Sinkkonen, 2014). Table 1 summarizes definitions of energy services presented in some of the most cited journal articles identified using the Web of Science.…”
Section: Defining the Energy Service Conceptmentioning
confidence: 99%
“…Much energy service research has focused on describing actual service usage in various countries, regions, or sectors (see, e.g., Bertoldi et al, 2006;Okay and Akman, 2010;Painuly et al, 2003;Vine, 2005) or specific contextual situations (see e.g., Mahapatra et al, 2013).…”
Section: Positioning the Study In Relation To Previous Research On Enmentioning
confidence: 99%